Comment on: "Is motorized treadmill running biomechanically comparable to overground running? A systematic review and meta-analysis of cross-over studies" - Dewolf, A. H.; Mesquita, R. M.; Willems, P. A. (Sports Medicine, 2020)
Comment on: "Is motorized treadmill running biomechanically comparable to overground running? A systematic review and meta-analysis of cross-over studies" (Van Hooren et al. 2020)